STUDI DAN KAJIAN DATA NUKLIR REAKTOR GENERASI-IV DENGAN SPEKTRUM NEUTRON CEPAT - Suwoto Suwoto; Zuhair Zuhair (Jurnal Fisika FLUX, 2013)
Abstract. STUDY AND ASSESSMENT OF GENERATION IV REACTOR NUCLEARDATA WITH FAST NEUTRON SPECTRA. Generation IV International Forum (GIF)has evaluated and assessed NES of Gen- IV and selected six potential types ofreactors to be deployed in the next decade. Those include GFR, LFR, SFR, MSR,SCWR and VHTR. The first three reactors were fast neutron spectrum applied and therest reactors were thermal neutron spectrum used. The study and assessment focusedon the nuclear data characteristic parameter and nuclear data uncertainties of Gen-IVreactor with fast neutron spectrum. Until 2008, the accuracy target of nuclear datacross-sections used it in fast reactor spectrum calculation are relatively significantespecially for σ-capture, σ-fission, and σ-inelastic. Several differences of nuclear datacross-sections on minor actinide isotopes between expected and targeted parametersare observed such as σ-fission of Cm-244 isotope up to 10 times larger and σ-captureof 92-U-238 isotope around 1.5-2 times higher than targeted parameters. Uncertaintyand accuracy of minor actinide cross-sections for fast spectrum Gen-IV reactorsprovide relatively significant discrepancies (1.3 to 10 times higher) in term of accuracybetween expected and targeted parameters. Some differences of provided results fromany experimental and assessment data with several evaluated nuclear data files for Pbare found. Some discrepancies on integral parameter of fast spectrum Gen-IV reactorsbetween expected and targeted such keff, void reactivity and Doppler effects, peakpower and burn-up are clearly observed. Accurate and precise cross-sections data ofradiation captured and threshold reaction cross sections such as (n,2n), (n,3n), (n,p),(n,α) are necessary for fast reactors.Keywords: cross-sections, fast neutron spectrum, GFR, LFR, SFR, uncertainty, targetaccuracy